2018
DOI: 10.1002/jctb.5628
|View full text |Cite
|
Sign up to set email alerts
|

An optimal blend of single autodisplayed cellulases for cellulose saccharification – a proof of concept

Abstract: BACKGOUND To date, it has been challenging to determine the optimal proportions of the individual cellulases in crude extracts and multienzyme systems to promote enzyme synergism. The application of single surface‐display of enzymes may obviate such challenges. This article presents a proof of concept of the optimal mixing of single surface‐displayed cellulases for cellulose hydrolysis using Simplex lattice mixture design. RESULTS The recently discovered maximized autotransporter‐mediated expression system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
(101 reference statements)
0
4
0
1
Order By: Relevance
“…In the current research, the simultaneous addition of cellulases (i.e., a blend of three cellulases) gave higher saccharification compared to the sequential addition of cellulases for 90 U of endoglucanase, 80 U of exoglucanase, and 220 U of -glucosidase. Obeng et al (2018) and Malgas et al (2020) also reported cellulase synergism for a cocktail of cellulases in enzymatic hydrolysis of biomass. However, the blend ratio and enzyme source were different, which might be responsible for the variation in results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the current research, the simultaneous addition of cellulases (i.e., a blend of three cellulases) gave higher saccharification compared to the sequential addition of cellulases for 90 U of endoglucanase, 80 U of exoglucanase, and 220 U of -glucosidase. Obeng et al (2018) and Malgas et al (2020) also reported cellulase synergism for a cocktail of cellulases in enzymatic hydrolysis of biomass. However, the blend ratio and enzyme source were different, which might be responsible for the variation in results.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the optimal amount of exoglucanase was required for a higher endoglucanase titer to prevent feedback inhibition. Similarly, a higher titer of glucosidase was required to prevent the feedback inhibition of endoglucanases and exoglucanases by cellobiose accumulation ( Obeng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…and Aspergillus terreus , respectively (GarciaKirchner and Huitron 1996 ). It is reported that a blend ratio of 1:1.6:1.4 of endoglucanase: exoglucanase: β-glucosidase was identified as the sweet spot for optimum sugar yield (Obeng et al 2018 ). Similary, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…La Figura 3 muestra los resultados de la RSM, la combinación de factores estableció que transcurridos 161 minutos se logran los mejores resultados del proceso de salado, al alcanzar un valor de actividad de agua de 0,95 y un contenido de sal de 0,042 g NaCl/g en la fase líquida, que corresponde a un valor de de 0,17 g de NaCl/g en base seca al utilizar sal ahumada con envasado al vacío, Figura 4(A); en este tipo de salado se aporta el sabor característico a humo que está relacionado con una mayor aceptación sensorial (Obeng et al, 2018).…”
Section: Modelización Y Maximización Del Proceso De Saladounclassified